The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/iej.13579
|View full text |Cite
|
Sign up to set email alerts
|

A novel three‐dimensionally printed model to assess biofilm removal by ultrasonically activated irrigation

Abstract: Aim To apply an innovative three‐dimensionally printed tooth model to investigate the efficacy of three ultrasonically activated irrigation (UAI) systems in removing multispecies biofilms from dentine samples. Methodology Three‐dimensionally printed teeth with a curved root canal were fabricated with a standardized slot in the apical third of the root to achieve precision fit of human root dentine specimens. Multispecies biofilms including Enterococcus faecalis, Streptococcus mitis and Campylobacter rectus wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Bhuva et al (2010) demonstrated that ultrasonic irrigation with NaOCl is superior to saline needle/syringe irrigation in biofilm removal at all three levels of the root canal [ 19 ]. Comparatively, other studies noted similar results, although the evaluation method of biofilm removal was different and included plate counting (CFU method) [ 41 , 44 , 45 ]. In addition, it was shown that ultrasonic NaOCl irrigation offers better bacterial reduction than ultrasonic irrigation with water or saline, which can be explained by the antimicrobial effect of NaOCl [ 30 , 33 ].…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Bhuva et al (2010) demonstrated that ultrasonic irrigation with NaOCl is superior to saline needle/syringe irrigation in biofilm removal at all three levels of the root canal [ 19 ]. Comparatively, other studies noted similar results, although the evaluation method of biofilm removal was different and included plate counting (CFU method) [ 41 , 44 , 45 ]. In addition, it was shown that ultrasonic NaOCl irrigation offers better bacterial reduction than ultrasonic irrigation with water or saline, which can be explained by the antimicrobial effect of NaOCl [ 30 , 33 ].…”
Section: Resultsmentioning
confidence: 74%
“…According to the reviewed articles, potential double origins, lab-adapted strains [ 15 , 16 , 18 , 19 , 20 , 21 , 24 , 26 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and clinically isolated E. faecalis were noted [ 25 ]. Types of E. faecalis strains which are most widely used by different authors and bacteria origin are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a modification of 3‐D printed teeth has been presented: a 3‐D printed tooth with a slot in the root, into which a dentine segment can be introduced, thus allowing investigation of the effects of root canal preparation on natural human dentine (Choi et al, 2021). Following growth of a biofilm and root canal instrumentation the dentine specimens were investigated using confocal laser scanning microscopy and field‐emission scanning electron microscopy (SEM).…”
Section: Experimental Models and Substrates For Studies On Root Canal...mentioning
confidence: 99%